New Technologies and the Effectiveness of the Environment Management System - JOPKIEWICZ, Szymon (Journal of Environmental Management and Tourism, 2023)
The goal of this study is to determine how well new technologies can help organizations' environment management systems (EMS). In order to collect and evaluate data from 60 individuals working for different firms who have implemented new technology in their EMS, the study uses a quantitative research approach. The study's findings imply that EMS efficacy in businesses is significantly enhanced by the deployment of modern technology. The study's conclusion urges organizations to adopt new EMS technologies in order to increase their environmental performance. Significant progress has been made in the area of environmental management thanks to new technologies. The purpose of the study was to look at how new technology could affect how successful the system for environmental management is (EMS). Data were gathered through a survey and were analyzed quantitatively. According to the study, emerging innovations have a beneficial effect on how well the EMS functions. The results imply that incorporating new technology into the EMS can result in environmental management practices that are more effective and efficient.